Cognitive Cities c - Shen, Jian.; Chang, Yao-Chung.; Su, Yu-Sheng.; Ogata, Hiroaki; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2020)
This book constitutes refereed proceeding of the Second International Cognitive Cities Conference, IC3 2019, held in Kyoto, Japan, in September 2019. The 37 full papers and 46 short papers were thoroughly reviewed and selected from 206 submissions. The papers are organized according to the topical sections on cognitive city for special needs; cognitive city theory, modeling and simulation; XR and educational innovations for cognitive city; educational technology and strategy in cognitive city; safety, security and privacy in cognitive city; artificial intelligence theory and technology related to cognitive city; Internet of Things for cognitive city; business application and management for cognitive city; big data for cognitive city; engineering technology and applied science for cognitive city; maker, CT and STEAM education for cognitive city.
Cognitive City for Special Needs -- Cognitive City Theory, Modeling and Simulation -- XR & Educational innovations for Cognitive City -- Educational Technology and Strategy in Cognitive City -- Safety, Security and Privacy in Cognitive City -- Artificial Intelligence Theory and Technology Related to Cognitive City -- Internet of Things for Cognitive City -- Business Application and Management for Cognitive City -- Big Data for Cognitive City -- Engineering Technology and Applied Science for Cognitive City -- Maker, CT and STEAM Education for Cognitive City.
Keywords: Database management; Computers; Computer engineering; 9; Social sciences -- Data processing; Artificial intelligence; Coding theory; Information theory; Database Management System; Computing Milieux; Computer Engineering and Networks; Computer Application in Social and Behavioral Sciences; Artificial Intelligence; Coding and Information Theory